KONSTRUKSI TULISAN MAHASISWA BILINGUAL DALAM MENULIS DESKRIPTIF - Mariam Ulfa; Kisyani Kisyani; Yuniseffendri Yuniseffendri (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2019)
As social creatures, humans live in a variety of diversity, ranging from culture, tradition, language, and habits. In terms of communication, most Indonesian people live in bilingual, Indonesian-language and local-language conditions, even multilingualism coupled with foreign language skills. Bilingual and multilingual conditions affect language skills, especially in writing skills. The results of this study show that Indonesian-regional bilingual students write better in Indonesian national languages compared to write in regional languages and in foreign languages (English). Many local language writings are interfered with in Indonesian because students assume that certain vocabulary is very difficult to find in local languages so that they are replaced with Indonesian. In terms of quantity of writing, on average most students produce more Indonesian language production than Madura, Javanese and foreign languages.